Usability Measurement and Evaluation of E-Learning to Support the Training Program for Academic Staff (Pengukuran Usability dan Evaluasi E-Learning untuk Program Pelatihan bagi Tenaga Kependidikan) - wati, theresia; Seta, Henki Bayu; Isnainiyah, Ika Nurlaili (Jurnal Pekommas, 2017)
This article discusses the usability measurement and evaluation of e-learning being used as a media for the academic staff training program of UPN "Veteran" Jakarta. E-learning system usability will be measured based on Nielsen heuristic approach and analyzed with five independent variabels, i.e. learnability, efficiency, memorability, error and satisfaction. The data collection involved 169 respondents from academic staff as e-learning application users. Based on the results of this study, it was found that the aspects of learnability, efficiency and memorability have a significant effect on usability.Artikel ini membahas mengenai pengukuran usability pada aplikasi e-learning serta evaluasi pemanfaatan e-learning sebagai media pelatihan keterampilan tenaga kependidikan UPN “Veteran” Jakarta. Dalam penelitian ini akan diukur tingkat usability sistem berdasarkan pendekatan heuristik Nielsen dan dianalisis dengan lima variabel bebas, yaitu learnability, efficiency, memorability, error dan satisfaction. Pengambilan data dengan kuesioner melibatkan 169 responden pengguna aplikasi e-learning untuk pelatihan tenaga kependidikan. Berdasarkan hasil penelitian, didapatkan bahwa aspek learnability, efficiency dan memorability berpengaruh signifikan terhadap usability.